The Landscape Changes in Mento Toelakan Plantation, 1863-1950s - Dennys Pradita; Adi Putra Surya Wardhana (History Department, Semarang State University and Historian Society of Indonesia, 2023)
This research studies the landscape change of Mento Toelakan Plantation in Wonogiri(Periode). Mento Toelakan was a private plantation located in the Duchy of Mangkunegaran. The existence of this plantation was a sign of the triumph of the liberal economic era. This research used a historical method, landscape, and environmental history approach. Several problems discussed were (1) the causes of the Mento Toelakan area experiencing the landscape change, (2) the forms of landscape change, and (3) the impact of the landscape change in Mento Toelakan Plantation Periode. The results showed that the landscape at the Mento Toelakan Plantation underwent landscape changes in several stages. The reason was the rented land by European investors and the political dynamics after the end of Dutch colonialism. First, land rent converted forest areas in Mento Toelakan into plantations. Second, coffee cultivation introduced the local society to coffee culture. Third, changing coffee plantations to agave plantations introduced the local community to natural fiber processing. Fourth, the Japanese military occupation used Mento Toelakan land for military purposes. Finally, the Mento Toelakan plantation was taken over by the village community to become dry land and rice fields in the independence era. This indicates that many factors, such as capitalism, politics, human activities, and nature itself, influenced the changing landscape of Mento Toelakan.Penelitian ini bertujuan untuk mengkaji perubahan lanskap Perkebunan Mento Toelakan di Wonogiri 1863-1950-an. Mento Toelakan merupakan perkebunan swasta yang berada di wilayah Kadipaten Mangkunegaran. Keberadaan perkebunan ini menjadi tanda kejayaan era ekonomi liberal. Eksploitasi modal asing memengaruhi perubahan lanskap di wilayah Mento Toelakan, Wonogiri. Penelitian ini menggunakan metode sejarah dan pendekatan lanskap dan sejarah lingkungan. Beberapa permasalahan yang dibahas adalah (1) penyebab area Mento Toelakan mengalami perubahan lanskap, (2) bentuk perubahan lanskap, (3) dan dampak perubahan lanskap Perkebunan Mento Toelakan 1863-1950-an(Periode) Hasil penelitian menunjukkan lanskap di Perkebunan Mento Toelakan mengalami perubahan lanskap dalam beberapa tahap. Penyebabnya adalah penyewaan lahan oleh pemodal swasta dan dinamika politik pasca berakhirnya kolonialisme Belanda. Pertama, sewa tanah yang dilakukan pemodal swasta mengubah area hutan di Mento Toelakan menjadi perkebunan. Kedua, budidaya kopi mengenalkan masyarakat dengan budaya kopi. Ketiga, mengubah perkebunan kopi menjadi perkebunan agave telah mengenalkan masyarakat dengan pengolahan serat alam. Keempat, pemerintah militer Jepang memanfaatkan lahan untuk kepentingan militer. Terakhir, perkebunan Mento Toelakan diambil alih oleh masyarakat desa sehingga menjadi tanah-tanah tegalan dan sawah pada era kemerdekaan. Dengan demikian, perubahan lanskap Mento Toelakan dipengaruhi oleh banyak faktor, seperti kapitalisme, politik, ulah manusia, dan alam itu sendiri.